Histochemistry and protein profile of the mandibular glands of workers of the ant Atta sexdens rubropilosa (Hymenoptera: Formicidae) - Favaro Pavon, Lorena [UNESP]; Camargo Mathias, Maria Izabel [UNESP] (International Society of Cytology, 2004)
Insect mandibular glands are always associated to the mandibles; they are part of the salivary glandular system. The mandibular glands are composed by a reservoir associated to the secretory cells, with each secretory cell connected to the reservoir by means of individual canaliculi. These glands play an important role in the production of pheromones, which are compounds involved in defense, communication, and reproduction of the colony. Mandibular glands of soldiers and major and minor workers of the ant Atta sexdens rubropilosa were processed for different histochemical tests, total protein content, and protein electrophoretic profile determination. The histochemical tests detected the presence of lipids, DNA/RNA, polysaccharides, and proteins at different regions of the gland. The protein electrophoretic profiles showed that the total protein content as well as the number of peptides of each caste follow a progressive order in relation to the size of the individual. Thus, we suggest that the production of secretion is directly linked to the task that the individual performs in the colony.
Keywords: Ants; Histochemistry; Mandibular Glands; Pheromones; Protein; Atta; Atta sexdens; Atta sexdens rubropilosa; Formicidae; Hymenoptera; Insecta